Screening of Metabolites and Metabolic Pathways in Five Different Ocimum Species From the Same Origin Using GC-MS - Ravi Prakash Jaiswal; Vishal Chugh; Sushil Nagar; Shalini Purwar; Akbare Azam; Ankit Verma (Biochemistry Research International, 2025)
This study presents the comparative and preliminary phytochemical analysis of essential oils extracted from 5 different Ocimum species, including Ocimum basilicum Linn, Ocimum canum Sims, Ocimum citriodorum, Ocimum gratissimum Linn and Ocimum sanctum Linn. The gas chromatography coupled with single quadrupole mass spectrometry was employed for the screening of the different metabolites. The present study investigates a total number of 111 bioactive compounds which were identified across the five Ocimum species, with O. citriodorum exhibiting the highest diversity. The analysis revealed significant variations in the chemical profiles, attributed to differing eco-climatic conditions. Key bioactive compounds, such as α-pinene, linalool and caryophyllene, were consistently found across species. The study also mapped these compounds to metabolic pathways, highlighting their roles in monoterpenoid, phenylpropanoid and sesquiterpenoid biosynthesis. Detailed analysis of O. basilicum, O. citriodorum, O. sanctum, O. canum and O. gratissimum oils demonstrated unique metabolic properties, with each species showing distinct pathway activations and dominant compounds. The findings were validated using principal component analysis and hierarchical clustering analysis, confirming the species’ chemical diversity and distinct clustering. This comprehensive characterization enhances our understanding of Ocimum spp. essential oils, offering valuable insights for their pharmaceutical, food and cosmetic applications.